2018
DOI: 10.1016/s0140-6736(18)30840-7
|View full text |Cite|
|
Sign up to set email alerts
|

Long-term albumin administration in decompensated cirrhosis (ANSWER): an open-label randomised trial

Abstract: Italian Medicine Agency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
357
2
15

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 396 publications
(398 citation statements)
references
References 33 publications
13
357
2
15
Order By: Relevance
“…In one study, long‐term treatment with albumin has been shown to be effective in preventing recurrence of ascites in patients with cirrhosis, while in another cohort of patients admitted for first onset of ascites, the chronic administration of albumin reduced not only ascites recurrence but also mortality . These results were recently confirmed in a large multicentre randomized clinical trial, showing that in patients with cirrhosis and non‐refractory ascites, long‐term administration of human albumin at the same doses used in our present study ameliorates the control on ascites formation, reduces complications and improves survival . On the other hand, in patients with cirrhosis in the waiting list for liver transplantation, Solà et al did not confirm a positive effect of albumin in association with midodrine on complications development and mortality, but it is noteworthy that the dose of albumin administered was half compared to the one used in our study.…”
Section: Discussionsupporting
confidence: 71%
“…In one study, long‐term treatment with albumin has been shown to be effective in preventing recurrence of ascites in patients with cirrhosis, while in another cohort of patients admitted for first onset of ascites, the chronic administration of albumin reduced not only ascites recurrence but also mortality . These results were recently confirmed in a large multicentre randomized clinical trial, showing that in patients with cirrhosis and non‐refractory ascites, long‐term administration of human albumin at the same doses used in our present study ameliorates the control on ascites formation, reduces complications and improves survival . On the other hand, in patients with cirrhosis in the waiting list for liver transplantation, Solà et al did not confirm a positive effect of albumin in association with midodrine on complications development and mortality, but it is noteworthy that the dose of albumin administered was half compared to the one used in our study.…”
Section: Discussionsupporting
confidence: 71%
“…It is also imperative that every effort should be made to treat or slow the progression of CKD in patients with cirrhosis. Although not specifically addressed in this study, the literature has reported that the regular use of albumin in patients with ascites can significantly reduce the incidence of renal dysfunction (defined as SCr >1.5 mg/dL/1.73 m 2 ) and HRS1, most likely related to improved hemodynamics in patients with decompensated cirrhosis and ascites. Likewise, the management of NAFLD or NASH with lifestyle changes or medications could potentially prevent the development of or delay the progression of CKD in these patients, although lifestyle changes may be more difficult to achieve than regular use of albumin.…”
Section: Discussionmentioning
confidence: 96%
“…Three studies assessing the effects of longterm albumin administration to patients with decompensated cirrhosis have been published in the current year. The ANSWER study, a multicenter, investigator‐initiated, open‐label, randomized trial enrolled 431 patients with cirrhosis and uncomplicated ascites requiring the daily administration of 200 mg of an antialdosteronic drug and 25 mg of furosemide . Patients were randomized to receive either standard medical treatment (SMT), which included albumin administration for well‐established indications, or SMT plus 40 g of albumin twice a week for the initial 2 weeks and then 40 g once a week.…”
Section: Available Evidence On the Effects Of Longterm Albumin Adminimentioning
confidence: 99%